A Multicenter Comparison of Inpatient Resource Use for Adult Spinal Deformity Surgery. Issue 7 (April 2016) - Hostin, Richard; Robinson, Chessie; O'Brien, Michael; Ames, Christopher; Schwab, Frank; Smith, Justin S.; Lafage, Virginie; Gupta, Munish; Hart, Robert; Burton, Douglas; Bess, Shay; Schaffrey, Christopher; et al.
Abstract : Study Design: Multicenter, retrospective analysis, prospective database, consecutive case series. Objective: This study examines multicenter variability in patient-level surgical resource use, including implants, biologics, and length of stay (LOS), alongside health-related quality-of-life (HRQoL) improvements after adult spinal deformity (ASD) surgery. Summary of Background Data: Efficiency in surgical resource use is critical to high-value health care. Decision makers and payers are placing increasing scrutiny on the costs and outcomes associated with complex spine surgery. Little is currently known regarding the variation in resources used and associated outcomes in complex spine surgeries. Methods: HRQoL outcomes were calculated from the Oswestry Disability Index, disease-specific 22-item Scoliosis Research Society questionnaire, and Medical Outcomes Study Short Form 36-question health survey domain scores. Changes in HRQoL were estimated as the difference between baseline and 2-year values. Patient-level surgical resources included blood use, bone morphogenetic protein volume, LOS, and implants. Patients were classified by mild, moderate, or severe sagittal modifier and analyzed across centers using analysis of variance and multivariable regression. Results: We analyzed 251 ASD patients, who were predominantly female (n = 207, 85%) with an average of 56 years (range 18–84 years). Significant differences were found in the average 2-year change in HRQoL across centers; however, this difference was found insignificant after controlling for patients within the same modifier groups ( P  > .05). However, significant differences were found across centers in average resources used per surgery ( P  < 0.05), with only LOS not reaching significance ( P  > 0.05). After accounting for clinical, demographic, and regional characteristics at the patient level, variation among centers persisted in resource use with no corresponding statistical differences in HRQoL outcomes. Conclusion: The use of additional surgical resources does not appear to impact 2-year HRQoL outcomes after surgery for ASD. The estimated impact of physician preference on surgical resource utilization highlights the variation in current surgical practice and the opportunity for cost reductions via a more standardized approach. Level of Evidence: 3